EDUCATION GAME AS AN EFFORT DELIGHTFUL LEARNING IN THE ELEMENTARY SCHOOL - Zainal Abidin; Nasrul; Sri Amerta; Vini Ariani Erwin; Rahmawati Erwin; Chandra; Yesi Anita; Annisa Kharisma (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This study aims to develop a thematic learning media in the era of industrial revolution 4.0 by using educational games for elementary students that are valid, practical and effective. Thematic learning media using educational games is closely related to innovation and the use of technology following the demands of the industrial revolution 4.0 era to increase student’s attractiveness in learning. Thematic media learning was the result of development by using adobe flash CS6 program. The contained of media was thematic learning that integrates of several subjects. The development model used was 4-D (define, design, develop, disseminate). The research data was obtained from the validity test (media validation sheet), practicality (student and teacher response questionnaire), and effectiveness (student learning activities and results). Data were analyzed descriptively. The results showed that the thematic learning media was valid (media content according to curriculum, attractive design and layout, ease of operation, easy to understand students' language, and clear presentation according to student characteristics), practical (clear contents and objectives, easy to read, attractive appearance, and student interest increases), and effective (can increase student activity and learning outcomes). Learning media using educational games can create a fun learning process.